Analysis of Financial Statements to Assess the Company's Financial Performance at PT. Midi Utama Indonesia Tbk - Fahmi Rizky; Laila Annisyah Lubis; Budi Dharma (Penerbit Jurnal Indonesia, 2023)
PT Midi Utama Indonesia, Tbk is one of the companies with the largest retail network in Indonesia established in 2007 and the holder of the Alfamidi store brand. As of 2019, Alfamidi has 1,555 outlets consisting of 1,538 Alfamidi outlets and 17 Super Alfamidi outlets spread across several islands in Indonesia and supported by more than 22,000 employees. The method in this determination uses the method of observation and literature study. In analyzing financial statement data, the analysis technique used is ratio analysis and it is concluded with respect to the company's financial performance. The ratios used are liquidity ratios, solvency ratios, profitability ratios and operating performance ratios. The results of the ratio calculation show that the company has a fairly good operational performance capability.